Peningkatan Kompetensi Menyusun Karya Ilmiah bagi Guru SMP Negeri 3 Saradan Kabupaten Madiun: Competence Improvement in Preparing Scientific Article for Teachers of State Junior High School 3 Saradan, Madiun District - Inna Kuswandari; Abdulloh Jaelani; Windarto Windarto (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Teachers are professional educators with the main task of educating, teaching, guiding, directing, training, assessing, and evaluating students in early childhood education, formal education, basic education, and secondary education. Teachers also have the responsibility to produce professional development works in the form of books, modules, or scientific articles. This is the background for implementing community service at SMPN 3 Saradan, Madiun, by the lecturers of the Mathematics Department, Faculty of Science and Technology, Universitas Airlangga. The step of community service activities includes how to write scientific papers, which is followed by assignments for the preparation of scientific papers for teachers as training output. The results of the feedback from the training participants showed a positive response from the participants regarding the selection of topics, the capabilities of the speaker, and the training facilities. Training activities attended by teachers accompanied by assignments and assistance in the preparation of scientific articles have succeeded in increasing teacher competence in making scientific articles. Furthermore, similar programs need to be priority programs for stakeholders, including schools and governments.